Darboux problem for the generalized Euler – Poisson – Darboux equation - Ismoilov, A. I.; Mamanazarov, A. O.; Urinov, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
In the article Euler – Poisson – Darboux equation was considered in the characteristic triangle and Darboux problem wasinvestigated. The solution of the problem was found by Riemann’s method. Theorems on the existence and uniqueness ofthe solution were proved.